2011
DOI: 10.1097/hp.0b013e31820dba65
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Radiation-Damaged Precursor Cells in Bone Marrow Based on Modeling of the Peripheral Blood Granulocytes Response

Abstract: Bone marrow failure is the major cause of radiation lethality in mammals. Since bone marrow is distributed heterogeneously within trabecular spongiosa encased in a cortex of cortical bone, it is very difficult to measure the extent of the radiation damage directly. However, indirect consequences of damage to marrow, such as reductions in peripheral blood cell counts, are easily measured. In this paper, the authors investgate a mathematical model of the granulopoiesis system that provides quantitative relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The organs of the blood and hematopoietic systems are vulnerable to radiation [10] [14] . Indeed, many studies have shown that radiation can cause a decrease in the visible components of blood [15] , cell morphology changes, alterations to the electrolyte state in peripheral blood (PB), mild hyperplasia in the bone marrow (BM) [16] , serious inhibition or even destruction of the bone marrow [17] , [18] , a reduction in the production of erythrocytes [19] , changes in the aggregation state of platelets [20] , and induction of the transformation of normal stem cells into tumor stem cells [20] [22] . Thus, a hemogram of the blood system is often used initially as an approximate guide to assess the adverse effects caused by radiotherapy to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…The organs of the blood and hematopoietic systems are vulnerable to radiation [10] [14] . Indeed, many studies have shown that radiation can cause a decrease in the visible components of blood [15] , cell morphology changes, alterations to the electrolyte state in peripheral blood (PB), mild hyperplasia in the bone marrow (BM) [16] , serious inhibition or even destruction of the bone marrow [17] , [18] , a reduction in the production of erythrocytes [19] , changes in the aggregation state of platelets [20] , and induction of the transformation of normal stem cells into tumor stem cells [20] [22] . Thus, a hemogram of the blood system is often used initially as an approximate guide to assess the adverse effects caused by radiotherapy to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Change in the cellular concentration in blood is one of the most important biomarkers to assess the extent of injury caused by acute radiation exposure (Hu & Cucinottam, ). Figures and show the responses of different blood cell types (lymphocytes, granulocytes, leukocytes, and platelets) to the Orion MPCV storm shelter radiation environment during the 5 × October 1989 SEP event (note that the storm shelter BFO dose rates are multiplied by a factor of 5), for male and female body types, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The organ dose estimate is based on a fitting procedure between the real‐time vehicle dosimeter measurements and a precomputed database of dose quantities calculated from the HZETRN radiation transport code (Slaba et al, ; Wilson et al, ), including the actual MPCV vehicle geometry and mass distribution. The estimated organ doses at the crew locations provide the necessary inputs to biological response models that predict clinically important syndromes associated with ARS and quantify radiation‐induced performance decrement (Hu & Cucinottam, ; Hu et al, , ). The active dosimeter‐based SEP organ dose estimate methodology presented in this paper will be tested operationally on NASA's Exploration Mission 1 (EM‐1) and fully utilized on NASA's EM‐2 (searched on 27 March 2018, https://www.nasaspaceflight.com/2012/06/nasa-teams-evaluating-iss-built-exploration-platform-roadmap/ and https://www.nasaspaceflight.com/2017/09/sls-em-1-em-3-notional-mission-outline/).…”
Section: Introductionmentioning
confidence: 99%
“…[12] In a study by Hu, after 3.3 Gy, 60 days were required for neutrophils to return to 95% of their normal values and for lymphocytes to return to 55% of their normal levels. [21] Also, Inoue et al showed radioresistant stem cell subfraction nine days after exposure to 4-6 Gy in mice. [22] Similarly, we found that 7 and 14 days after 5 Gy TBI, almost 20% of leucocytes and lymphocytes were radioresistant, possibly by means of radioresistant stem cells.…”
Section: Tablementioning
confidence: 99%